2020
DOI: 10.1371/journal.pcbi.1007782
|View full text |Cite
|
Sign up to set email alerts
|

Expression of quasi-equivalence and capsid dimorphism in the Hepadnaviridae

Abstract: Hepatitis B virus (HBV) is a leading cause of liver disease. The capsid is an essential component of the virion and it is therefore of interest how it assembles and disassembles. The capsid protein is unusual both for its rare fold and that it polymerizes according to two different icosahedral symmetries, causing the polypeptide chain to exist in seven quasi-equivalent environments: A, B, and C in AB and CC dimers in T = 3 capsids, and A, B, C, and D in AB and CD dimers in T = 4 capsids. We have compared the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 78 publications
2
23
0
Order By: Relevance
“…Figure S10 shows that the diamond pentamer can be found either bound to three or two double-stranded regions in the context of a capsid. Moreover, these results show that the HBV assembly pathway proceeds by the formation of diamond pentamers and dodecamers, instead of through the fivefold symmetric pentamer, as also supported by recent electron microscopy experiments ( 40 ).…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Figure S10 shows that the diamond pentamer can be found either bound to three or two double-stranded regions in the context of a capsid. Moreover, these results show that the HBV assembly pathway proceeds by the formation of diamond pentamers and dodecamers, instead of through the fivefold symmetric pentamer, as also supported by recent electron microscopy experiments ( 40 ).…”
Section: Resultssupporting
confidence: 83%
“…Our results indicate that the diamond-shape pentameric arrangement of Cps is a critical participant in HBV assembly, as a minimal stable structure of Cps able to condense single-stranded nucleic acids. Previous studies have reported the accumulation of small HBV assembly intermediates for truncated versions of Cp (without the CTD) and in the absence of nucleic acids ( 34 , 40 , 42 44 ). The assembly model proposed here (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Assembly proceeds most likely by a nucleation mechanism (comparable to the induction of crystallization from an oversaturated solution when a “crystal seed” is added), i.e., the rate-limiting assembly step is the formation of an intermediate (the nucleation seed) to which additional dimeric subunits can be added (see Figure 3 ), in the elongation phase, on a downhill energetic path [ 164 ]. The likely nucleation seed for neat CTD-less Cp derivatives such as Cp149 is a three-fold symmetric trimer of dimers [ 165 ], as supported by recent EM evidence [ 132 ]; this study identified, in addition, a two-fold symmetric pentamer as another predominant intermediate; there, two more dimers are associated to a trimer of dimers so as to generate two adjacent triangles. Considering that each Cp dimer is tetravalent ( Figure 7 ) the trigonal trimer of dimers saturates 6 of the 12 valencies, the two-fold symmetric pentamer 12 of the totally 20 valencies; hence these arrangements minimize the number of free valencies.…”
Section: Overall Structural Dynamics Of Hbv Cpsupporting
confidence: 57%
“…Recombinant CLPs from most Cps also assemble to >90% into T = 4 particles, except for heavily truncated derivatives such as Cp140. However, both forms can bind CAMs [ 131 ] and the presence of CAMs during assembly could affect their ratio as the particle types display subtle but distinct differences in subunit conformation and stability [ 132 ].…”
Section: Overall Structural Dynamics Of Hbv Cpmentioning
confidence: 99%
“…A recent study reported that the linker is relevant to HBV replication (e.g., pgRNA packaging, viral DNA synthesis, and the ratio of complete to empty virions) [40]. Recent reports provide an excellent overview about the structure of the different types of core dimers and capsids [41,42].…”
Section: Introductionmentioning
confidence: 99%